Evaluación de eficiencia de equipos multidisciplinarios en la elaboración diseños de proyectos de ingeniería civil mediante KPIs. - Pánchez Hernández, Vilma Esperanza (2024)
More information is needed about the efficiency of the work team that carries out design for the construction industry, a stage at which the project's development depends on and determines its cost. A multidisciplinary team is responsible for the design and must achieve performance in line with the expectations of the client and the design office. However, the way to measure the work teams' performance is incipient, and a set of indicators has not been defined reliably to allow it. This study aims to determine the performance of the technical work team, for which a set of indicators was established after a bibliographic review and expert opinion. The results of this study made it possible to measure the performance of design offices internationally and carry out comparative evaluations to facilitate their management in search of continuous improvement.